Crime induced poverty traps - Halvor Mehlum; Karl Ove Moene; Ragnar Torvik (University of Oslo, Department of Economics, 1999)
A dynamic macroeconomic model is used to analyze the interaction between economic growth, labor demand and crime. Due to endogenous crime, the model exhibits increasing returns to aggregate capital at certain development levels. At other development levels, however, there are decreasing returns to aggregate capital. The linkages determining the outcome work via aggregate labor demand and aggregate production. Hence, the increasing (or decreasing) return is external to the individual firm. The economy has potentially two stable equilibria: a) One where crime rates are high and capital stock, labor demand, and income is low. b) One where crime rates are low and capital stock, labor demand, and income is high. Equilibrium a) has the characteristics of a poverty trap. The existence of a poverty trap has important implications for the implementation of economic reforms. We show that a big bang reform, intended to improve efficiency, may throw the economy into a vicious circle of increasing crime and stagnation.
Keywords: 330; Kriminalität; Arbeitsangebot; Wirtschaftswachstum; Kriminalitätsökonomik; Theorie